Lifestyle And Metabolic Syndrome In Administrative Staff Of The First Republican University Of Peru And America (The Review of Diabetic Studies, 2025)
Objective: To correlate the lifestyle and metabolic syndrome factors in the administrative workers of the universidad nacional of Trujillo.Material and Methods: A stratified random sample of 168 administrative workers (men and women) from the universidad nacional of Trujillo, located in northern Peru, was selected during 2023. A questionnaire was developed to evaluate the lifestyle based on the level of physical activity, and a data collection form was used to record the metabolic syndrome factors.Results: The majority of men and women were active (42.48%), while 33.34% were sedentary and 24.18% had a very active lifestyle. Likewise, men and women presented with overweight (>26 kg/m2), high limits of triglycerides (160 mg/dl), and hypertension (>120/80 mmHg). Women also presented with low HDL (